2019
DOI: 10.1016/j.ijppaw.2019.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Parasites in brains of wild rodents (Arvicolinae and Murinae) in the city of Leipzig, Germany

Abstract: Small rodents serve as intermediate or paratenic hosts for a variety of parasites and may participate in the transmission of these parasites into synanthropic cycles. Parasites with neuroinvasive stages, such as Toxoplasma gondii or Toxocara canis, can cause detrimental damage in the brain of intermediate or paratenic hosts. Therefore, the occurrence of neuroinvasive parasite stages was evaluated in brains of wild rodents captured in the city of Leipzig, Germany. In addition, a few specimens from the cities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 70 publications
(90 reference statements)
0
10
1
1
Order By: Relevance
“…In Poland, there are no current data concerning T. gondii prevalence in wild, small rodents, thus the results of the present study can have new epidemiological value. T. gondii prevalence among rodents and insectivores (8.6% in mice, voles, common shrew and moles, and 6.3% in muskrats) in the current study showed moderate values; however, this is higher than the prevalence found in free-living rodents in the Czech Republic (1%) [28], and in yellow-necked mice in Germany (2.7%) [29]. The prevalence found in the current study in muskrats (6.3%) is lower than in the Czech Republic, where it ranged between 9-47% [30].…”
Section: Discussioncontrasting
confidence: 69%
“…In Poland, there are no current data concerning T. gondii prevalence in wild, small rodents, thus the results of the present study can have new epidemiological value. T. gondii prevalence among rodents and insectivores (8.6% in mice, voles, common shrew and moles, and 6.3% in muskrats) in the current study showed moderate values; however, this is higher than the prevalence found in free-living rodents in the Czech Republic (1%) [28], and in yellow-necked mice in Germany (2.7%) [29]. The prevalence found in the current study in muskrats (6.3%) is lower than in the Czech Republic, where it ranged between 9-47% [30].…”
Section: Discussioncontrasting
confidence: 69%
“…Wild rodents pose a particular threat for human communities because they constitute the most abundant and diversified group of all living mammals [7] and often adopt a synanthropic existence. Although some zoonotic parasites are not transmissible directly from rodents to humans, or pose just a low risk of direct transmission, predation of rodents by carnivore pets may cause infections in these animals, leading to subsequent contamination of households and other human-related environments [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…We designed a timesaving, tissue-clearing digestion technique by adapting and optimizing several published protocols (Dubey, 1998b;Mayer-Scholl et al, 2017;Waindok et al, 2019) for other organ tissues. As helminths are sensitive to HCl (Dubey, 1998a), incubation times are key for retrieving non-damaged specimens, and why a shorter and non-destructive protocol was needed so to preserve worms' integrity for identifying characteristics (Dubey, 1998a(Dubey, , 1998b.…”
Section: Methodsmentioning
confidence: 99%